2011
DOI: 10.1002/eco.213
|View full text |Cite
|
Sign up to set email alerts
|

Importance of groundwater and macrophytes for the nutrient balance at oligotrophic Lake Hampen, Denmark

Abstract: An ecohydrological study was carried out at an oligotrophic seepage lake, Lake Hampen, Denmark, to determine the seepage in and out of the lake and determine the mass budgets for nutrients. The lake is primarily surrounded by forest, although there are agricultural fields bordering a small portion of the lake perimeter. The water and mass balances indicate that there is a groundwater input of 1643 × 103 m3 year−1 into the lake (∼70% of total input) and a groundwater output of 1997 × 103 m3 year−1. The groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The analysis of the nutrient circulation system in oligotrophic lakes is an area of continuing research [ Oliveira Ommen et al , 2011]. At the same time, field experiments that identify the incidence of high‐frequency, large‐amplitude internal waves continue to be carried out and to provide insight into their wave structure, amplitude, and seasonality [ Preusse et al , 2012; Hutter , 2011, chapter 2].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the nutrient circulation system in oligotrophic lakes is an area of continuing research [ Oliveira Ommen et al , 2011]. At the same time, field experiments that identify the incidence of high‐frequency, large‐amplitude internal waves continue to be carried out and to provide insight into their wave structure, amplitude, and seasonality [ Preusse et al , 2012; Hutter , 2011, chapter 2].…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater, while seeping through lake sediments, may mobilize phosphorous from iron oxides, phosphorous-bearing minerals, and organic matter buried in lake sediments [10,13]. Although phosphorous was long considered to be immobile in groundwater, there is increasing evidence that the eutrophication of lakes is driven by groundwater discharge rich in phosphorous and that this may be an important albeit so far neglected source [47][48][49][50][51]. For instance, studies of the eutrophic Lake Arendsee (Germany) revealed that groundwater discharge was responsible for more than 50% of the total phosphorus supply to the lake [48].…”
Section: Groundwater-borne Phosphorous Fluxmentioning
confidence: 99%
“…For instance, studies of the eutrophic Lake Arendsee (Germany) revealed that groundwater discharge was responsible for more than 50% of the total phosphorus supply to the lake [48]. The importance of groundwater-borne phosphorous may also hold for oligotroph lakes [49].…”
Section: Groundwater-borne Phosphorous Fluxmentioning
confidence: 99%
“…This method is elaborate and prone to errors due to the small head differences, which are difficult to measure (Fritz and Mackley 2010). Ommen et al (2012) used a combination of hydraulic gradients between piezometers and the lake in combination with seepage meters to assess the volume of LGD and infiltration.…”
Section: Introductionmentioning
confidence: 99%